In suit growth of ultradispersed NiCo2S4 nanoparticles on graphene for asymmetric supercapacitors. (10th September 2015) - Xiao, Yuanhua; Su, Dangcheng; Wang, Xuezhao; Zhou, Liming; Wu, Shide; Li, Feng; Fang, Shaoming
Abstract: We present a facile one-step solvothermal approach for in situ growth of ultradispersed nickel cobalt sulfide (NiCo2 S4 ) nanoparticles on the graphene (GR) sheets without adding any surfactant. When acting as an electrochemical supercapacitor electrode material, the NiCo2 S4 @GR delivers a highly improved specific capacitance of 1708 F g −1 at a current density of 1.0 A g −1, compared with that of free NiCo2 S4 (950 F g −1 ). The performances of NiCo2 S4 @GR electrode material can also be optimized by carefully tailoring the amount of each ingredient NiCo2 S4 and GR in the nanocomposites. Asymmetric supercapacitor devices based on these NiCo2 S4 @GR nanocomposites and aqueous electrolyte showd a long-term cycling ability with a high-energy density (68.5 Wh kg −1 at 850.0 W kg −1 ) and a high-power density (17.0 kW kg −1 at 37.7 Wh kg −1 ), implying its great potential application in high-performance energy storage devices.